1982
DOI: 10.1037/0033-2909.91.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Consumer satisfaction with mental health treatment.

Abstract: This article reviews the literature on the evaluation of consumer satisfaction with mental health treatment. The methods of assessing consumer satisfaction, the methodological issues in studies assessing satisfaction, the results of the studies, and the value of consumer evaluation are discussed. Consumer evaluation is found to be a useful though flawed method of assessing services, and it should be included in a multimethod treatment evaluation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
190
0
10

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(214 citation statements)
references
References 94 publications
12
190
0
10
Order By: Relevance
“…Parent satisfaction was positively associated with the number of treatment sessions. Several other studies have reported a positive relationship between duration of treatment and satisfaction (Brannan et al, 1996;Godley et al, 1998;Lebow, 1982), but the causal direction of the relationship is not known (i.e., satisfied patients may attend more sessions and/or increased duration of treatment may improve satisfaction. We are not aware of studies reporting an effect of therapist experience on satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Parent satisfaction was positively associated with the number of treatment sessions. Several other studies have reported a positive relationship between duration of treatment and satisfaction (Brannan et al, 1996;Godley et al, 1998;Lebow, 1982), but the causal direction of the relationship is not known (i.e., satisfied patients may attend more sessions and/or increased duration of treatment may improve satisfaction. We are not aware of studies reporting an effect of therapist experience on satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Context indicators, patient outcome and impact indicators were not included. This does mean that the evaluation methodology is comprehensive enough to escape much of the criticism against such studies quoted by Lebow (1982).…”
Section: Discussionmentioning
confidence: 99%
“…In a review article on consumer satisfaction with mental health treatment, Lebow (1982) identifies many methodological problems with this kind of research at that time. Reliability of instruments are seldom addressed, and the validity of the studies can be questioned on many fronts.…”
Section: Patient Satisfaction Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniformly high levels of satisfaction with services has been identified as a threat to the validity of customer satisfaction questionnaires (Lebow, 1982). It is important, therefore, to demonstrate that instruments used to collect data on children's satisfaction do not produce uniformly high evaluations of all services and are able to detect differences between services, or a difference following a change in a service.…”
Section: Validitymentioning
confidence: 99%